Molecular characterization of acute hepatopancreatic necrosis disease causing Vibrio parahaemolyticus strains in cultured shrimp Penaeus monodon in south‐west farming region of Bangladesh (Dhaka University Journal of Biological Sciences, 2018)
Acute hepatopancreatic necrosis disease (AHPND) is an emerging shrimp disease caused by strains of Vibrio parahaemolyticus containing a unique virulent plasmid, responsible for substantial economic losses since 2009; caused up to 100% mortality in farmed shrimp Penaeus monodon. The purpose of this study was to isolate and identify the pathogenic strain of V. parahaemolyticus causing AHPND in cultured shrimp (Penaeus monodon) using classical and molecular techniques. Samples were collected from three different locations of south-west shrimp farming regions of Bangladesh viz. Sadar Upazilla of Satkhira; Mongla and Morrelganj under Bagerhat district. In this study, three selective media were used for primary isolation of V. parahaemolyticus. Among 46 primary isolates, 18 representative isolates were checked for the species-specific detection of V. parahaemolyticus using ldh primers and all of them were found to be positive. 16S rRNA gene sequencing were used to further confirm the isolates as V. parahaemolyticus. tdh primer was used to check human pathogenicity but all 18 isolates showed negative result. The isolates were further characterized to check their AHPND positivity using AP3 and AP4 primers. Ten isolates showed positive results for AP3 (55.56%) and 9 showed positive results for AP4 (50%) which indicated that the isolates were AHPND positive. This study also reported that all AHPND positive strains were resistant to the antibiotic gentamycin but sensitive to chloramphenicol, nalidixic acid, nitrofurantoin and tetracycline. The findings of this study will help the shrimp farmers and policy makers to take proper biosecurity measures to protect shrimps from AHPND and thereby sustain the shrimp production in Bangladesh.Dhaka Univ. J. Biol. Sci. 27(1): 57-68, 2018 (January)